A corpus separatum elszakadása a Magyar Királyságtól: Fiume 1918. november 4. - Hamerli, Petra (Acta Scientiarum Socialium, 2018)
After the Great War, in autumn 1918 the nationalities of the Austro–Hungarian Monarchy proclaimed their independence. Croatia, which formed a personal union with the Hungarian Kingdom for centuries, was recognized to be an independent state by the Hungarian Government. The Croatian Committee formed in London in 1915 expressed its willing to be part of a federalist South-Slavic state. In this way Hungary lost its only one port, the city of Fiume, as territorically it was part of the Istria. Nevertheless, it was not obvious that Croatia could keep Fiume – Rijeka –, as the Italian National Council of the city formed on 30 October 1918 proclaimed its belonging to Italy through a petition written on 4 November 1918 to the prime minister Vittorio Emanuele Orlando, as the majority of the Fiumean citizens were Italians. This petition made Italy to claim Fiume on the Paris Peace Conference held in 1919, although it was not judged or promised to the Italians in the secret Treaty of London of 1915 that made Italy to enter into the war. The question of Fiume caused serious conflict among Italy and Yugoslavia, and – as the Peace Conference gave the city to the Yugoslavian Kingdom – in autumn 1919 the Italian poet Gabriele D’Annunzio decided to annex Fiume and create a city state. In my paper I will present, through the case of Fiume, what consequences an only day – in this case the 4 November 1918 – can have in history.
Keywords: Great War (1914‒1918); history of Central-Europe; History of Hungarian Kingdom; Fiume (Rijeka)